The final forest : big trees, Forks, and the Pacific Northwest - Dietrich, William, 1951- (University of Washington Press, 2010)
"Before Forks, a small town on Washington's Olympic Peninsula, became famous as the location for Stephenie Meyer's Twilight book series, it was the self-proclaimed "Logging Capital of the World" and ground zero in a regional conflict over the fate of old-growth forests. Since Pulitzer Prize-winning journalist William Dietrich first published The Final Forest in 1992, logging in Forks has given way to tourism, but even with its new fame, Forks is still a home to loggers and others who make their living from the surrounding forests. The new edition recounts how forest policy and practices have changed since the early 1990s and also tells us what has happened in Forks and where the actors who were so important to the timber wars are now."--Pub. desc.